Schizophrenia and mysticism: a conceptual analysis - Hammond, Carol Anne (Rhodes University, Faculty of Humanities, Department of Psychology, 1981)
From introduction: The aim of this thesis is to explore the "queer relationship'" existing between mysticism and madness as it emerges from psychological writings and to examine and re-evaluate the life of Joan of Arc in terms of the conceptual framework that emerges.
Keywords: Schizophrenia; Mysticism